Journal of the Meteorological Society of Japan - Horinouchi, Takeshi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Journal of the Meteorological Society of Japan (JMSJ) is an international, peer-reviewed, and open-access journal for the publication of research in areas of meteorology. The journal's broad scope includes meteorological observations, modeling, assimilations, analyses, global and regional climate research, satellite remote sensing, chemistry and transport, and dynamic meteorology including geophysical fluid dynamics. In particular, JMSJ welcomes papers related to Asian monsoons, climate and mesoscale models, and numerical weather forecasts.
Keywords: Earth sciences; Geography; Climatology; Atmospheric science; Earth sciences; Earth and Environmental Sciences; Climate Sciences; Atmospheric Science; Earth Sciences